Management and Scheduling of Spine Surgery in a Level 1 Trauma Center in the Setting of the COVID-19 Pandemic: Feasibility and Considerations for Reimplementation of Elective Spine Surgery. (3rd September 2022) - Crawford, Zachary; Elson, Nora C.; Kanhere, Arun; Thomson, Cameron; Sabbagh, Ramsey; Nasser, Rani; Guanciale, Anthony F.
Introduction: Determination of what constitutes necessary surgery in the setting of acute hospital resource strain during the COVID-19 pandemic is an unprecedented challenge for healthcare systems. Over the past two years during the COVID-19 pandemic, there have been many changes in reviews of medically necessary spine surgery. There continues to be no clear guidelines on recommendations and further discussion is necessary to continue to provide appropriate and high-level care during future pandemics. Significance: This review critically appraises and evaluates current barriers to medically necessary spine surgery during the COVID-19 pandemic and evaluates future decision making to maintain spine surgery during future pandemics or limitations in medical care. Results: Multiple studies included in this review have shown that while various orthopaedic surgeries may be considered elective, medically necessary spine surgery will need to continue during settings of limited medical care. This review discussed multiple methods and recommendations to limit transmission of virus from patients to providers and providers to patients. Conclusion: Continued medically necessary spine surgery in the setting of the COVID-19 pandemic and future pandemics should continue while limiting risk of transmission to continue providing high-level medical care and allowing hospitals to maintain financial responsibility.